2017
DOI: 10.1371/journal.pone.0172912
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically distinct weight loss by 10,12 CLA and caloric restriction highlight the importance of subcutaneous white adipose tissue for glucose homeostasis in mice

Abstract: BackgroundWidely used as a weight loss supplement, trans-10,cis-12 conjugated linoleic acid (10,12 CLA) promotes fat loss in obese mice and humans, but has also been associated with insulin resistance.ObjectiveWe therefore sought to directly compare weight loss by 10,12 CLA versus caloric restriction (CR, 15–25%), an acceptable healthy method of weight loss, to determine how 10,12 CLA-mediated weight loss fails to improve glucose metabolism.MethodsObese mice with characteristics of human metabolic syndrome wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 65 publications
10
64
1
1
Order By: Relevance
“…Although LCA‐treated flies experienced a significant extension of their lifespans, they also registered higher glucose levels (Figure c) while the triglyceride (Figure SF1a, Supporting Information) and protein (Figure SF1b, Supporting Information) levels remained unchanged. This observation is in contrast to findings from other reports showing that lower glucose levels are associated with lifespan extension . Indeed, Schulz and co‐workers have demonstrated an extended lifespan in glucose‐restricted C. elegans depending on the activated AAK‐2, the mammalian AMPK ortholog.…”
Section: Discussioncontrasting
confidence: 95%
“…Although LCA‐treated flies experienced a significant extension of their lifespans, they also registered higher glucose levels (Figure c) while the triglyceride (Figure SF1a, Supporting Information) and protein (Figure SF1b, Supporting Information) levels remained unchanged. This observation is in contrast to findings from other reports showing that lower glucose levels are associated with lifespan extension . Indeed, Schulz and co‐workers have demonstrated an extended lifespan in glucose‐restricted C. elegans depending on the activated AAK‐2, the mammalian AMPK ortholog.…”
Section: Discussioncontrasting
confidence: 95%
“…Intraperitoneal glucose (1 mg kg −1 ) and insulin (0.75 U kg −1 ) tolerance tests were performed after a 4 h fast as described previously (Subramanian et al, 2008). Body composition was measured non-invasively in conscious immobilized mice (n = 7-8 mice per group) using quantitative magnetic resonance (EchoMRI whole body composition analyser; Echo Medical Systems, Houston, TX, USA) by the University of Washington Nutrition Obesity Research Center Energy Balance Core, as described previously (den Hartigh et al, 2017). All analyses were performed in a blinded manner.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…As such, CLA supplement users ingest significantly more 10,12 CLA than would be obtained from the diet. Supplemental CLA promotes significant weight loss in animals and modest weight loss in humans, an effect now attributed to the 10,12 CLA isomer [ 4 ]. We have previously shown that 10,12 CLA reduces lipid accumulation by increasing fatty acid oxidation in a cell line derived from (mouse) 3T3 cells (3T3-L1) adipocytes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that 10,12 CLA reduces lipid accumulation by increasing fatty acid oxidation in a cell line derived from (mouse) 3T3 cells (3T3-L1) adipocytes [ 5 ]. Moreover, obese mice supplemented with 10,12 CLA lose body weight and fat mass due to enhanced fatty acid oxidation with increased energy expenditure and white adipose tissue browning [ 4 ]. These changes in energy expenditure are not the result of weight loss per se, as a control group undergoing caloric restriction to mirror weight loss by the 10,12 CLA-supplemented group did not exhibit these changes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%